The crosstalk between microbiota and metabolites in AP mice: an analysis based on metagenomics and untargeted metabolomics - Zhou, Qi; Tao, Xufeng; Guo, Fangyue; Zhu, Yutong; Wu, Yu; Xiang, Hong; Shang, Dong (Frontiers in Cellular and Infection Microbiology, 2023)
Background and purpose: The microbiota dysfunction aggravated the severity of acute pancreatitis (AP), but the relationship between microbiota dysfunction and metabolites alteration was not fully explained. This study aimed to explore the crosstalk between microbiota and metabolites in AP mice. Methods: Experimental AP models were established by caerulein for 7 times plus lipopolysaccharide (LPS) for once in C57/BL mice. To reveal systemic disturbance of AP, metagenomics and untargeted metabolomics were applied to reveal systemic disturbance of microbiota and metabolites in AP progress, respectively. Results: Gut microbiota from AP mice was mainly composed of Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria, and presented a “core microbiota” characterized by an expansion in Proteobacteria as well as a decrease in Actinobacteria. Kyoto encyclopedia of genes and genomes (KEGG) analysis found that the significantly differential microbiota was involved in several signaling networks. Moreover, 872 metabolites were identified from untargeted metabolomics. Among them, lipids and lipid-like molecules were majorly affected. The integrated analysis of metagenomics and metabolomics showed that acetate kinase (Acka) was associated with various gut microbiota, including Alistipes, Butyricimonas and Lactobacillus. Particularly, Acka was tightly correlated with the metabolite daphnoretin. Besides, the functional gene of O-acetyl-L-serine sulfhydrylase (Cysk) was correlated with Alistipes, Jeotgalicoccus and Lactobacillus, and which was associated with metabolites of bufalin and Phlorobenzophenone. Conclusion: Our study uncovered the relationship between gut microbiota and metabolites during AP, especially the Lactobacillus, Alistipes and Butyricimonas associated functional genes (Acka and Cysk) was tightly correlated to anti-inflammation and anti-tumor metabolites (daphnoretin and bufalin).